The development of EFL Learners’ willingness to communicate and self-efficacy: The role of flipped learning approach with the use of social media - Fan, Xiangping (Frontiers in Psychology, 2022)
The promotion of English as a Foreign Language (EEL) learners’ willingness to communicate and self-efficacy in different contexts has drawn the attention of many investigators. This review explored the effect of digital-based flipped learning classrooms on the enhancement of learners’ willingness to communicate and self-efficacy. The related literature indicated that learners’ intention to communicate is affected by the use of social media and digitalized materials used in flipped classrooms. Compared to the traditional educational contexts, this review showed higher levels of self-efficacy in flipped classrooms among EFL learners. Furthermore, the review expounded on the implications and future directions for EFL teachers, teacher educators, educational policy-makers, and advisors. The ideas can improve their awareness of learner self-efficacy, willingness to communicate, and the use of flipped learning approach in educational contexts.